A new Leuconostoc citreum strain discovered in the traditional sweet potato sour liquid fermentation as a novel bioflocculant for highly efficient starch production. (June 2021) - Wang, Xuan; Zhao, Liang; Wang, Yongtao; Xu, Zhenzhen; Wu, Xiaomeng; Liao, Xiaojun
Graphical abstract: Highlights: Bacterial composition changes in sweet potato sour liquid fermentation were profiled. Seven isolates showed starch-flocculating abilities with flocculation rates up to 55.56%. First time to report the starch flocculation functions of Leuconostoc citreum. Highly efficient starch sedimentation was achieved using new strain L. citreum SJ-57. Abstract: Sour liquid fermentation is commonly used in the sedimentation process of traditional starch production, where bacteria play a critical role in starch flocculation. In this study, the dynamic changes of bacterial compositions during sweet potato sour liquid (SPSL) fermentation were profiled using the single-molecule real-time (SMRT) sequencing, unveiling that Leuconostoc citreum, Leuconostoc pseudomesenteroides, Lactococcus lactis, and Lactobacillus plantarum were the dominant microorganisms in the process, and Leuconostoc citreum exhibited a strong positive correlation with starch flocculation rate (FR). In total, 75 lactic acid bacterial (LAB) strains were isolated from the SPSL, but only 7 of them caused starch flocculation. For the first time, Leuconostoc citreum strains were reported with excellent starch-flocculating abilities (up to 55.56% FR in 20 min), which might be attributed to their ability to connect starch granules through the cell surface to form large aggregation. This study provides a comprehensive understanding of the bacterial dynamics in SPSL fermentation at the species level. A starch flocculation yield of 93.63% was achieved within 1 h by using the newly discovered Leuconostoc citreum SJ-57. The time required for total starch sedimentation was reduced from 10 h to 4 h, compared with the traditional process. These results suggest that this novel bioflocculant is more suitable for modernizing the traditional SPSL fermentation process and achieving rapid and highly efficient starch sedimentation.